A 4-Year Follow-Up Study of Attention-Deficit Hyperactivity Symptoms, Comorbidities, and Psychostimulant Use in a Brazilian Sample of Children and Adolescents with Attention-Deficit/Hyperactivity Disorder - Palma, Sonia M. M.; Natale, Ana Carolina M. P.; Calil, Helena M. (Frontiers in Psychiatry, 2015)
The aim of this study was to evaluate symptom persistence in attention-deficit/hyperactivity disorder (ADHD), the development of comorbidities, and psycho-stimulant usage patterns. Follow-up studies were conducted in 37 patients with ADHD and 22 healthy controls, aged 10 and 18, four years after their first assessment. The ADHD was rated as persistent if participants met all DSM IV criteria for syndromic or sub-threshold persistence, or had functional impairments (functional persistence). Of the 37 ADHD patients we reevaluated, 75% had persistent symptoms, and psychiatric comorbidities with additional functional impairments and academic problems were more common than in controls. These follow-up findings show a high comorbidity associated with ADHD and support the importance of evaluation and treatment for ADHD and comorbidities throughout life.